Specific Pharmacological Profile of A2A Adenosine Receptor Predicts Reduced Fractional Flow Reserve in Patients With Suspected Coronary Artery Disease. Issue 8 (11 September 0207) - Paganelli, Franck; Resseguier, Noémie; Marlinge, Marion; Laine, Marc; Malergue, Fabrice; Kipson, Nathalie; Armangau, Pauline; Pezzoli, Nicolas; Kerbaul, Francois; Bonello, Laurent; Mottola, Giovanna; Fenouillet, Emmanuel; et al.
Abstract : Background: The rapid and reliable exclusion of myocardial revascularization is a major unmet clinical need in patients with suspected coronary artery disease (CAD) and non‐contributive electrocardiography and troponin. Non‐invasive tests have high rates of false positives and negatives, and there is no biomarker to assess myocardial ischemia. The presence of spare adenosine A2A receptors (A2 A R)—characterized by a high dissociation constant/half maximal effective concentration (KD /EC50 ) ratio—expressed on peripheral blood mononuclear cells (PBMC) has been associated with ischemia during exercise stress testing in patients with CAD. In this work, we investigated the diagnostic accuracy of spare A2 A R versus fractional flow reserve (FFR) in patients with suspected CAD. Methods and Results: Sixty patients with suspected CAD, but non‐contributive electrocardiography and troponin, were consecutively enrolled in this prospective study. The binding (KD ), functional response (cyclic adenosine monophosphate [cAMP] production; EC50 ) on PBMC A2 A R were compared with FFR results. Patients were divided into 3 groups: 17 (group 1) with normal coronary angiography (n=13) or stenosis <20% (n=4); 21 with CAD and non‐significant FFR (group 2); and 22 with CAD and significant FFR (group 3). Median KD /EC50 was 6‐fold higher in group 3 (4.20; interquartile range: 2.81–5.00) than group 2 (0.66; interquartile range: 0.47–1.25) and 7‐fold higher than group 1 (0.60; interquartile range: 0.30–0.66). Conclusions: In patients with suspected CAD and non‐contributive electrocardiography and troponin, the absence of spare A2 A R on PBMC may help to rule out myocardial ischemia. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT03218007.